Software Architecture Superstream Series : Soft Skills Are the Hardest Part - Ford, Neal; Ford, Neal; Hohpe, Gregor; Helfand, Heidi; Wardin, Kate; Simmons, Anjuan; Asthagiri, Nimisha (O'Reilly Media, Inc., 2021)
Developers and architects like to solve technical problems, not people problems. However, as Gerald Weinberg was famous for saying, "No matter what they tell you, it's always a people problem." Exceptional interpersonal skills--teamwork, facilitation, and leadership among them--are at least half of what it takes to become an effective software architect (regardless of the actual role or title an architect may have). But attaining the skills that will ensure you can communicate clearly and get stakeholder buy-in can be a difficult proposition. Join us for this Superstream event to learn more about these essential skills, understand why they're so critical, and see how you can start putting them into practice. What you'll learn and how you can apply it Explore techniques to analyze and select the right architecture patterns Discover ways to diagram and document an architectural solution Learn better communication skills to champion architecture decisions to developers and stakeholders This course is for you because ... You're a senior-level developer who wants to make the move to architect. You're a practicing software architect who wants to hone your skills and learn new software architecture techniques and practices. You want to learn more about how to succeed as a software architect by developing your leadership and negotiation skills. Recommended follow-up: Read The Software Architect Elevator (book) Read Dynamic Reteaming, second edition (book) Read Microservices Patterns (book) Take Mastering Technical Presentations by Example (live online training course with Neal Ford) Read Fundamentals of Software Architecture (book) Read Building Microservices, second edition (book) Read Building Evolutionary Architectures (book) Read Building Event-Driven Microservices (book) Take Software Architecture by Example (live online training course with Mark Richards and Neal Ford) Take Architecture: The Hard Parts (live online training course with Mark Richards and Neal Ford) Take Microservice Fundamentals (live online training course with Sam Newman)